Highly Accelerated Stress Screening Optimization - Jamadin, Nor Hasnifarina (2016)

(untitled)
Highly Accelerated Stress Screening (HASS) a popular method used by many manufacturing facilities to screen process defects. HASS testing comprises of two phases – (i) precipitation and (ii) detection. The detection includes a functional test at various temperature values and vibration test at 6-degree of freedom. Primary actuator control electronic (PACE) product has high customer returns due to product failure at different temperature in the field. Therefore, this research investigates the compliance in temperature profile used for PACE testing with HASS standard. Proof of Screen (POS) and data collection have shown that product control HASS testing resulted in accurate outcome. A further improvement from 2-16 % in temperature profile is achieved via process control. Process-control improved screen effectiveness to the product by minimizing the error to the set point limit. Mean Square Error (MSE), Normalize Cross Correlation (NCC), and statistical analysis tools are used to verify the process-control improvement profile result. MSE shows that improvement around 5% in minimizing the error and NCC improvement shows around 3% and 19.5% for detection and precipitation phases respectively.